The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1002/ange.201903956
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Initiated Bulk‐Scale Free‐Radical Polymerization

Abstract: Mechanical initiation of polymerization offers the chance to generate polymers in new environments using an energy source with unique capabilities.R ecently,arenewed interest in mechanically controlled polymerization has yielded many techniques for controlled radical polymerization by ultrasound. However,o ther types of polymerizations induced by mechanical activation are rare,e specially for generating high-molecular-weight polymers.H erein is an example of using piezoelectric ZnO nanoparticles to generate fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
0
21
0
2
Order By: Relevance
“…In addition to the chemical effects, ultrasonication also provides physical forces to reduce the degree of entanglement and increase the free volume of the chains, so the diffusional limitation caused by the increased viscosity in mechanoATRP is alleviated 25‐34 . From the viewpoint of free volume theory, ultrasonic intensity and frequency serve as the important influencing factors to free‐volume fitting parameters ( β kj ) 4,31 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the chemical effects, ultrasonication also provides physical forces to reduce the degree of entanglement and increase the free volume of the chains, so the diffusional limitation caused by the increased viscosity in mechanoATRP is alleviated 25‐34 . From the viewpoint of free volume theory, ultrasonic intensity and frequency serve as the important influencing factors to free‐volume fitting parameters ( β kj ) 4,31 .…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al presented a kinetic insight into mechanoATRP at high conversion under solution and bulk conditions 20 . Besides, mechanoATRP was also explored in the presence of ZnO piezoelectric nanoparticles 18,29 . In addition to piezoelectric effect, ultrasound‐induced radical formation without piezoelectric nanoparticles has been developed for ATRP (e.g., sonoATRP) in both aqueous medium 30‐32 and organic solvent 33,34 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, relative to control DN gels, RSE provides this fatigue resistance while also suppressing the loss in modulus that accompanies energy dissipation. Third, prior examples of mechanochemically induced changes in macroscopic physical properties involve either activation in solution (21,39), irreversible plastic deformation (40,41), and/or the presence of reagents beyond the initial network (11,39,41); we are not aware of direct correlations of macroscopic properties and mechanochemical response within an intact strand. Mechanophore designs offer an increasing range of responses (42), and the chemical changes that accompany reactive chain extension might be designed to produce additional, desirable responses.…”
Section: Main Textmentioning
confidence: 97%
“…14,20 Esser-Kahn et al have demonstrated the piezoelectrically mediated atom transfer radical polymerization (mechano-ATRP) by piezoelectric activation of Cu(II) deactivator and bulk-scale free radical polymerization initiated by piezoelectric generation of alkyl radicals. [20][21][22] Later on, they disclosed piezoelectrically activated thiol-ene polymerization and disulfide bond cross-linking that opened up new avenues for sulfur-based polymer chemistry. 23,24 However, the further development of piezo-polymerization is deterred, as the less attention was put on the reversible deactivation radical polymerization (RDRP) techniques other than ATRP.…”
Section: Main Textmentioning
confidence: 99%
“…[34][35] We hypothesize that the adsorption of tris(2-pyridylmethyl)amine (TPMA) on ZnO surface could balance the screening charges and fuel the electron transfer to alkyl bromides. 20,22 We first investigated this piezoelectrically mediated RAFT (piezo-RAFT) polymerization of n-butyl acrylate (BA) under US (40 kHz). As a result, the resulting poly(n-butyl acrylate) (PBA) showed excellent control over molecular weight and high chain-end fidelity as evidenced by matrixassisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS).…”
Section: Main Textmentioning
confidence: 99%